Fight Club - Palahniuk, Chuck (Vintage, 2003)
The rise of a terrorist organization, led by a waiter who enjoys spitting in people's soup. He starts a fighting club, where men bash each other, and the club quickly gains in popularity. It becomes the springboard for a movement devoted to destruction for destruction's sake